AGAINST PHENOMENAL EXTERNALISM - ELISABETTA SACCHI; ALBERTO VOLTOLINI (Crítica, 2017)
We maintain that no extant argument in favor of phenomenal external- ism (PE) is really convincing. PE is the thesis that the phenomenal properties of our experiences must be individuated widely insofar as they are constituted by worldly properties. We consider what we take to be the five best arguments for PE. We try to show that none of them really proves what it aims at proving. Unless better arguments in favor of phenomenal externalism show up in the debate, we see no reason to relinquish an idea that seems intuitive and appeals to many cognitive sci- entists: that phenomenology is narrow, i.e., that phenomenal properties are intrinsic properties of our experiences. This idea grounds the opposite philosophical position, phenomenal internalism (PI).